JENIS DAN KELIMPAHAN NYAMUK (DIPTERA: CULICIDAE) DI DESA BANJAR SARI KECAMATAN ENGGANO KABUPATEN BENGKULU UTARA - Helmiyetti, Helmiyetti; Kurnia, Nuril Septianisa; Yahya, Yahya (Universitas Bengkulu, 2019)
Mosquitoes, one of the insects groups that have a high interaction with humans with a wide spread and cosmopolite. Factors that influence the spread of mosquitoes are the form of topography of an area and environmental factors. The aim of this research was to determine the type and abundance of mosquitoes (Diptera: Culicidae) in Banjarsari Village, Enggano District, North Bengkulu. The research was conducted in December 2018 to March 2019 with the sampling method of purposive sampling and capture of mosquitoes carried out by the Human Landing Collection and Resting Collection methods. The time of catching mosquitoes starts in the morning at 06.00-08.00 WIB, afternoon at 15.00-17.00 WIB and at night 18.00-24.00 WIB. The mosquito was identified in the Laboratory of Animal Physiology, Department of Biology, Faculty of Mathematics and Natural Sciences, Bengkulu University. The results of this research were analyzed in a qualitative frequency distribution with 3 groups of categories: many, medium and few categories. The types of mosquitoes obtained consisted of 5 types including Aedes albopictus, Armigeres subalbatus, Culex bitaeniorhynchus, Culex solitarius and Culex quinquefasciatus. The abundance of mosquitoes with many categories is found in Aedes albopictus and the abundance of categories with few species is found in Culex solitarius mosquitoes.